PERFORMANCES ASSESSMENT OF NATURAL REFRIGERANTS AS SUBSTITUTES TO CFC AND HCFC IN HOT CLIMATE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Due to the environmental concerns ozone depletion potential (ODP) and global warming potential (GWP) of the existing refrigerants, industry and researchers in this field are investigating long-term solutions. With extensive work on alternatives to chlorofluorocarbons (CFCs) and hydro chlorofluorocarbons (HCFCs), initially hydro fluorocarbons were considered to be long-term solutions. The global warming of HFCs has become a hurdle to accept them as long-term solutions. Now, the focus is on the use of natural refrigerants like hydrocarbons (HCs) such R290, R600, ammonia, carbon dioxide and water. These natural substances have very low GWP, and a zero ODP. This paper presents simulation results through a thermodynamic analysis of R22 and three of its alternatives natural refrigerants (R290, R600a and R717) for A/C and refrigeration purposes operating under various outdoor temperatures, represented by the condenser temperatures. The examined new refrigerants show varying performance, depending on the evaporator temperatures, but in every case, the condenser temperature seems to have an important impact on the performance of the cycle.